Nonlinear essential maps of Mönch, 1-set contractive demicompact and monotone (S)+ type. (2001) - Agarwal, Ravi P.; O'Regan, Donal
Abstract : In this paper the notion of an essential map is extended to a wider class of maps. Here we show if F is essential and F ≅ G, then G has a fixed point.